Follicular Unit Extraction with or without Platelet Rich Plasma in the Treatment of and Rogenetic Alopecia - Ali Khashaba, Ahmed; Nabil El Sadek, Alaa; Fikry Mehanna, Ayman; Mahmoud Mohammed Rabie, Moataz (International Journal of Psychosocial Rehabilitation, 2021)
Androgenetic alopecia (AGA) is a genetically determined phenomenon that is defined by gradual loss and reduction of normal thick hair follicles. This study aimed to determine if Platelet Rich Plasma (PRP) assists in Follicular Unit Extraction (FUE) or not This is a prospective comparative study that was performed in the period from January 2019 to January 2020 in Plastic & Reconstructive Surgery Department of Zagazig University Hospitals. This study included 16 patients with androgenic alopecia checked at Plastic Surgery Outpatient Clinic, Zagazig University Hospitals. Patients included in the study was divided into two groups according to receiving RPR or not, Group (1); 8 Patients treated with FUE with PRP. Group (2); 8 Patients treated with FUE without PRP.